Correlates of Sedentary Behaviour in Adults with Intellectual Disabilities-A Systematic Review - Oppewal, Alyt; Hilgenkamp, Thessa I. M.; Elinder, Liselotte Schafer; Freiberger, Ellen; Rintala, Pauli; Guerra-Balic, Myriam; Gine-Garriga, Maria; Cuesta-Vargas, Antonio; Oviedo, Guillermo R.; Sansano-Nadal, Oriol; Izquierdo-Gomez, Rocio; Einarsson, Ingi; et al. (International Journal of Environmental Research and Public Health, 2018)
Individuals with intellectual disabilities (ID) are at high risk for high levels of sedentary behaviour. To inform the development of programmes to reduce sedentary behaviour, insight into the correlates is needed. Therefore, the aim of this study is to review the evidence on correlates of sedentary behaviour in adults with ID. We performed a systematic literature search in Ovid Medline, Ovid Embase, Web of Science and Google Scholar up to 19 January 2018, resulting in nine included studies that were published from 2011 to 2018. Correlates were categorized according to the ecological model. Studies predominantly focused on individual level correlates. Of those correlates studied in more than one study, having epilepsy was associated with less sedentary behaviour and inconsistent results were found for sex, genetic syndromes, weight status, physical health, mobility, level of ID, and mental health. Of the few interpersonal and environmental factors studied, only living arrangements were studied in more than one study, with inconsistent results. To date, we have limited and inconclusive evidence about correlates of sedentary behaviour in adults with ID. Only when future studies unravel correlates and determinants, across all domains of the ecological model, will the potential opportunities to improve health by reducing sedentary behaviour come within reach.
EVALuna2:211433